Financing with preferential credit to coordinate the capital-constraint supply chain. Issue 21 (2nd November 2022) - Cheng, Yuxiang; Olson, David L.; Dolgui, Alexandre
ABSTRACT: This paper investigates the impacts of preferential credit policy, faced by capital constraint retailers, on coordinating the supply chain. Apart from different bank's and manufacturer's risk preferences, preferential credit is also affected by the retailers' exogenous collateral. We establish the preferential credit coordinating model (PCCM) to examine the optimal decisions and coordinate the supply chain with different financing channels, such as the preferential bank loan, preferential trade credit and portfolio credit. In this paper, we conclude some critical findings. Firstly, we find that the retailer's optimal would improve its optimal order quantity in the coordinated supply chain when he finances from a risk-pursuing bank or the manufacturer. Secondly, the retailer's financial cost would be shared with the manufacturer whether the retailer utilises preferential trade credit or bank financing channel. Thirdly, the capital constraint retailer would prefer preferential trade credit to the other financing methods for the purpose that the preferential trade credit could improve the coordinated supply chain's efficiency. Finally, we capture different impacts of collateral and risk preference on the supply chain. This article supplements the existing literature on supply chain finance with a preferential credit insight into the condition of the coordinated supply chain.